African Journal of Governance and Public Leadership (AJoGPL) - BC, Basheka; Dominique, E. Uwizeyimana (2022)
African Journal of Governance and Public Leadership (AJoGPL) is a peer reviewed quarterly journal. AjoGPL seeks to promote academic scholarship and publishing of original manuscripts in Public Administration, Management, Governance, Leadership, Public Policy, Public Leadership and related fields